Women’s individual and joint property ownership: Effects on household decisionmaking - Doss, Cheryl; Kim, Sung Mi; Njuki, Jemimah; Hillenbrand, Emily; Miruka, Maureen (International Food Policy Research Institute, 2014)
In this paper, the relationship of women’s individual and joint property ownership and the level of women’s input into household decisionmaking is explored with data from India, Mali, Malawi, and Tanzania. In the three African countries, women with individual landownership have greater input into household decisionmaking than women whose landownership is joint; both have more input than women who are not landowners.